Central Banks: The Spiritual and Religious Legacy of Mother Teresa of Calcutta in Commemorative Coins - Orlando Carmelo Castellanos Polo; Sol Beatriz Vélez Escobar; María Victoria Agudelo Vargas (Pharos Journal of Theology, 2025)
This article analyzes the link between theology, collective memory, and the symbolic representation of holiness through commemorative coins issued by central banks, focusing on the figure of Mother Teresa of Calcutta. From a theological perspective, it examines how issuing institutions such as the Vatican, India, Albania, and other countries have used coins as a means of disseminating spiritual, ethical, and humanitarian values. These numismatic pieces represent, in metal and design, the life testimony of a woman who embodied Christian love for the poorest and most marginalized. The research adopts an interdisciplinary approach that articulates symbolic theology, spiritual economy, and commemorative numismatics, recognizing coins not only as economic instruments but also as vehicles of silent evangelization and social pedagogy. The findings show that, by minting figures of holiness, commemorative coins contribute to preserving spiritual memory in public spaces, integrating the sacred into everyday life.